Recurrent plunging ranula - Santosh Kumar Swain (Wolters Kluwer Medknow Publications, 2024)
A ranula is a cystic swelling containing mucous that manifests on the floor of the oral cavity. Typically, it displays as a soft, bluish, and well-defined swelling, enveloped by an epithelial lining. The ranulas are of two types: such as simple ranula and plunging ranula. Ranula is developed due to the accumulation of secretions of sublingual salivary glands above the mylohyoid muscle, whereas plunging ranula results from the collection of mucus along the fascial planes of the neck. Trauma is a common cause of mucous extravasation and accumulation in the surrounding tissues, which results in ranula. Recurrence of ranula, particularly plunging ranula, is very uncommon. This case report describes a recurrent case of plunging ranula in a young adult, which is an extremely rare incidence in clinical practice.